1987
DOI: 10.1139/f87-323
|View full text |Cite
|
Sign up to set email alerts
|

Abundance Patterns and Community Attributes of Fishes Relative to Environmental Gradients

Abstract: Marshall, T. E., and P. A. Ryan. 1987. Abundance patterns and community attributes of fishes relative t o environmental gradients. Can. I. Fish. Aquat. Sci. M(Suppl. 2): 198-215.Seventy-five lakes s f the Canadian boreal forest were examined for patterns of fish species abundance and community structure in relation to gradients of four environmental variables: (1) Bake area, (2) mean depth,(3) Secchi disk transparency, and (4) rnorpkoedaphic index (MEI). Mean depth appeared to exert the greatest control o n th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 38 publications
3
30
0
Order By: Relevance
“…We found that high altitude or deep lakes sustain populations of sensitive/intolerant fish species such as salmonids (trout, char), bullhead and coregonids, while shallow and relatively small lakes were characterized mainly by phytophilic and benthivoroustolerant species. This is in line with numerous studies in the northern hemisphere showing that enhanced primary productivity reinforced by specific morphometric characteristics of shallow lakes leads to a shift in fish communities from Salmoniformes (mainly coregonids) to phytophilic or tolerant species (Marshall & Ryan, 1987;Persson et al, 1991;Holmgren & Appelberg, 2000;Mehner et al, 2005;Garcia et al, 2006). Furthermore, at species level, Heino et al (2010) found that pike and perch were among the most common species in meso-eutrophic boreal lakes, while brown trout was common in deep oligotrophic lakes in the same region.…”
Section: Discussionsupporting
confidence: 78%
“…We found that high altitude or deep lakes sustain populations of sensitive/intolerant fish species such as salmonids (trout, char), bullhead and coregonids, while shallow and relatively small lakes were characterized mainly by phytophilic and benthivoroustolerant species. This is in line with numerous studies in the northern hemisphere showing that enhanced primary productivity reinforced by specific morphometric characteristics of shallow lakes leads to a shift in fish communities from Salmoniformes (mainly coregonids) to phytophilic or tolerant species (Marshall & Ryan, 1987;Persson et al, 1991;Holmgren & Appelberg, 2000;Mehner et al, 2005;Garcia et al, 2006). Furthermore, at species level, Heino et al (2010) found that pike and perch were among the most common species in meso-eutrophic boreal lakes, while brown trout was common in deep oligotrophic lakes in the same region.…”
Section: Discussionsupporting
confidence: 78%
“…The coldwater stenothermal nature of lake trout is well documented, and several authors have synthesized studies of lake trout thermal ecology (Christie and Regier 1988;MacLean et al 1990;Evans 2007). The requirements for cold, oxygenated water by the four coldwater taxa present in Minnesota followed the same general order observed by Marshall and Ryan (1987) in Ontario lakes.…”
Section: Discussionmentioning
confidence: 97%
“…Surface area and some measure of depth were previously found to be useful variables for predicting species associations Schneider 1981;Tonn et al 1983;Marshall and Ryan 1987). A large surface area may correspond to more habitat area or volume for fish (Christie and Regier 1988), and depth and area describe lake morphometry, which affects most physical, chemical, and biological processes within lakes (Wetzel 1975).…”
Section: Discussionmentioning
confidence: 99%